2015
DOI: 10.1517/14728222.2016.1085972
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the glial-derived neurotrophic factor and related molecules for controlling normal and pathologic pain

Abstract: Introduction: GDNF and its family of ligands (GFLs) have several functions in the nervous system. As a survival factor for dopaminergic neurons, GDNF was used in clinical trials for Parkinson's disease. However, GFLs their receptors are potential targets for new pain-controlling drugs. Such a potential should not be underestimated because molecules with analgesic activities in rodents mostly failed to be effective in translational studies. Areas covered:The circuitry, molecular and cellular mechanisms by which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 115 publications
1
24
0
Order By: Relevance
“…This study revealed a novel mechanism of TNFα inhibitors in neuropathic manifestation normalization involves the inactivating of neurotrophic receptor‐expression nociceptors, Ret(+) neurons. Generally, glial cell line‐derived neurotrophic factor (GDNF) regulates the function and morphology of the Ret receptor and is used as an analgesic agent that acts as a ligand to the Ret receptor [29–31]. Sensitization of Ret(+) neurons was reported to mediate the development of mechanical allodynia [7], and the current study demonstrated the changes in TNFα content and Ret(+) neuronal profiles in a parallel fashion.…”
Section: Discussionsupporting
confidence: 51%
“…This study revealed a novel mechanism of TNFα inhibitors in neuropathic manifestation normalization involves the inactivating of neurotrophic receptor‐expression nociceptors, Ret(+) neurons. Generally, glial cell line‐derived neurotrophic factor (GDNF) regulates the function and morphology of the Ret receptor and is used as an analgesic agent that acts as a ligand to the Ret receptor [29–31]. Sensitization of Ret(+) neurons was reported to mediate the development of mechanical allodynia [7], and the current study demonstrated the changes in TNFα content and Ret(+) neuronal profiles in a parallel fashion.…”
Section: Discussionsupporting
confidence: 51%
“…These observations lead one to hypothesize that the use of Ret inhibitors may offer a novel therapeutic approach for the treatment of IBS [108]. Thus, GFLs and their receptors are potential targets for new inflammatory pain-controlling drugs [109,110].…”
Section: In Pain Sensitivitymentioning
confidence: 99%
“…These subunits constitute the tetrodotoxin-resistant Na + channels, which are expressed at high levels in nociceptive neurons of the DRG. The expression of these channels avoids the decay of conduction velocity after axotomy (Cummins et al, 2000 ); hence, and as other authors have proposed, GDNF modulates nociception (Merighi, 2016 ; Salio and Ferrini, 2016 ).…”
Section: Regulation Of Pain and Nociceptionmentioning
confidence: 89%
“…Alternatively, the administration of gliafin, a peptide agonist for the GDNF receptor, induces RET phosphorylation, but studies related to pain reduction are still in progress (Garcia-Bennett et al, 2013 ). The small molecule XIB4035, which binds to GFRα1, has been topically administered to alleviate neuropathic pain in a rodent model of diabetes and achieved excellent results (Merighi, 2016 ). The mechanisms elicited by GDNF are not completely elucidated, but seem to involve a decrease in excitability and glutamate release (Salio et al, 2014 ), even under physiological conditions (Merighi, 2016 ).…”
Section: Regulation Of Pain and Nociceptionmentioning
confidence: 99%
See 1 more Smart Citation